The Development of a Flibook-Based Interactive E-Module to Facilitate Sequences and Series Learning Process for 10th-Grade - Muhammad Afan Bisri; Atik Wintarti; Shofan Fiangga (Program Studi S1 Matematika UNESA, 2023)
The use of textbooks during the learning process makes it less interactive because textbooks only focus on presenting content and neglect the motivation and activities of their users. This study aims to describe the development process of a flipbook-based interactive E-module to facilitate the independent series and sequences learning process and to determine its validity, practicality, and effectiveness. The development of the E-module used the Plomp design research model, which consists of 3 phases: preliminary research, prototyping phase, and assessment phase. The quality of the developed E-module refers to valid, practical, and effective criteria. The results of this study are 1) in the preliminary research, an analysis of needs and problems, a review of the literature, and create a conceptual framework were conducted; 2) in the prototyping phase, designing and developing the E-module using Flip PDF Professional software and testing the validity of the content & media were conducted, the content validity test scored 97.33% (very valid), the construct (media) validity test scored 91.16% (very valid); 3) in the assessment phase, practicality and effectiveness tests were conducted for 1 class of 10th-grade students, the practicality test scored 78.04% (practical), and the effectiveness test got an average N-gain score of 0.7 (high level of effectiveness). Thus, the developed E-module has valid, practical, and effective criteria to facilitate independent series and sequences learning processes.